Stimulation of the migratory capacity of rat nerve tissue culture cells under the influence of the conditioned medium for fibroblast-like adipose tissue cells - Liubych, Larysa; Staino, Larysa; Yehorova, Diana (Problems of Environmental Biotechnology, 2021)
Investigation of the neuroregenerative effect of the conditioned medium of fibroblast-like cells of rat adipose tissue in the culture of rat neural cells in vitro was carried out.